Market-based vs. grassroots citizen participation initiatives in photovoltaics: A qualitative comparison of niche development. (April 2016) - Hatzl, Stefanie; Seebauer, Sebastian; Fleiß, Eva; Posch, Alfred
Highlights: Citizen participation initiatives are a social innovation for a sustainable future. Market-based and grassroots CPIs differ in key processes and development phases. Currently, both types rarely emerge from local niche status towards regime level. Growth (market-based) or replication (grassroots) may drive regime influence. Both types depend on continued feed-in tariffs for their economic viability. Abstract: Photovoltaic citizen participation initiatives (CPIs) receive increasing attention as a form of social innovation, contributing to a sustainable decentralized energy future. However, their ability to outgrow a protected niche characterized by feed-in tariffs, to regime level, is unclear. Drawing on qualitative interviews with key actors, the present study classifies Austrian CPIs in terms of them being market-based (profit-oriented business) or grassroots initiatives (civil-society based community activism), and compares these two types with respect to the three key processes of strategic niche management: actor network formation, learning, and expectations management. Market-based CPIs exhibit a relatively heterogeneous external actor network. They follow a policy of business development, engage in highly professionalized learning, and access a large, widespread customer base. In contrast, grassroots CPIs leverage a tightly-knit network of local actors, engage in informal learning and shared expectations. In some CPIs, market-based and grassroots motivations converge. Both types seem capable of achieving regime level, either through individual growth or by aggregation of multiple small-scale initiatives. As yet, few CPIs have outgrown their local niche status. This is mainly due to a lack of intermediary actors which may institutionalize knowledge and resources to support the foundation of new CPIs.